Rancang Bangun Website Lelang Mobil menggunakan Framework Codeigniter 3 pada PT.ABC - Surya, Alfin Adi; Haromain, Imam (LPPM STT Terpadu Nurul Fikri, 2023)
An auction is a public sale of goods by oral or written bidding to achieve the highest price. PT.ABC is an auction company engaged in car auctions. PT.ABC is still using conventional methods for auction activities. The conventional system has several disadvantages, including manual recording, vulnerability to loss, and bidders being required to come to the location to buy auction items. This research builds a car auction website to improve the efficiency of the auction business. The application was built using the CodeIgniter 3 Framework using the MySQL database and web socket technology, Socket.IO. The software development method uses the waterfall method. Data collection was carried out by interview and observation at PT.ABC obtained data on the needs of the online auction system, the flow of car auction activities, and the things participants need to take part in the auction. Application development used a modeling concept, namely UML. The application was tested using a user acceptance test with 5 respondents for the admin and 24 people for the front-end. Evaluation results show that the application is very feasible to use and helps the process of running a business, with results from the questionnaire for the admin website at 93% and the front-end website at 91.67%.